Identification of a novel Candida metapsilosis isolate reveals multiple hybridization events. Issue 1 (25th October 2021) - O'Brien, Caoimhe E; Zhai, Bing; Ola, Mihaela; Bergin, Sean A; Ó Cinnéide, Eoin; O'Connor, Ísla; Rolling, Thierry; Miranda, Edwin; Babady, N Esther; Hohl, Tobias M; Butler, Geraldine
Abstract: Candida metapsilosis is a member of the Candida parapsilosis species complex, a group of opportunistic human pathogens. Of all the members of this complex, C. metapsilosis is the least virulent, and accounts for a small proportion of invasive Candida infections. Previous studies established that all C. metapsilosis isolates are hybrids, originating from a single hybridization event between two lineages, parent A and parent B. Here, we use MinION and Illumina sequencing to characterize a C. metapsilosis isolate that originated from a separate hybridization. One of the parents of the new isolate is very closely related to parent A. However, the other parent (parent C) is not the same as parent B. Unlike C. metapsilosis AB isolates, the C. metapsilosis AC isolate has not undergone introgression at the mating type-like locus. In addition, the A and C haplotypes are not fully collinear. The C. metapsilosis AC isolate has undergone loss of heterozygosity with a preference for haplotype A, indicating that this isolate is in the early stages of genome stabilization.